Mobility diminution in a nano-mosfet due to carrier injection from the ohmic contacts - Riyadi, Munawar A. (American Institute of Physics, 2011)
The mobility is being ballistic when the mean free path in a nanoscale transistor exceeds the channel length. The ballistic mobility is modeled and interpreted by analyzing transient velocity response to the electric field. The new model includes the transit-time delay that may become comparable to or smaller than the scattering-limited mean free time. For an applied voltage of 0.1 V or lower, the transient response effect degrades the mobility below its long-length limit. The model includes the carrier injection from the Ohmic contacts which can explain the mobility diminution in the nanoscale MOSFET. As a result, the new model shows excellent agreement with the ballistic mobility experimental data.